DYNAMIC RESPONSE OF THE LAYERING ORDER OF 2024 ALUMINUM ALLOY THIN PLATES AGAINST THE BIRD STRIKE - YUAN JiaJun (Jixie qiangdu, 2018)
In the aerospace sector,foreign object damage（ FOD） is a serious threat to the normal operation of aircraft and aviation security and bird strike damage is the most common. Based on AUTODYN finite element software,a bird bullet SPH model and a Lagrange model of 2024 aerospace aluminum alloy target are built to study the dynamic response and damage characteristic of aircraft envelope when subjected by bird strike. By comparing the simulation result with the experimental data,the validity of bird bullet SPH model is verified. Exploring the influences of largest drum kits,stresses and energies of target impacted by bird strike at different target laminates and bird strike velocities,the best target stack mode would be selected.